If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -2(2t + -1) Reorder the terms: 15 = -2(-1 + 2t) 15 = (-1 * -2 + 2t * -2) 15 = (2 + -4t) Solving 15 = 2 + -4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4t' to each side of the equation. 15 + 4t = 2 + -4t + 4t Combine like terms: -4t + 4t = 0 15 + 4t = 2 + 0 15 + 4t = 2 Add '-15' to each side of the equation. 15 + -15 + 4t = 2 + -15 Combine like terms: 15 + -15 = 0 0 + 4t = 2 + -15 4t = 2 + -15 Combine like terms: 2 + -15 = -13 4t = -13 Divide each side by '4'. t = -3.25 Simplifying t = -3.25
| 45-5n= | | (w^2+8w+12)(3w-27)=0 | | 5q-7=6q | | -4(3b+1)+(13b-5)=0 | | 8-(6-2)=11 | | 3x^2-3x+3=0 | | 4.9q-2.6-4.2q=-0.3q-1.6 | | x-12*6=9 | | 3x-2-2x=5+2x-2x | | -4m-36=8 | | 69(y-73)=-65 | | 5x-4x^2=0 | | 11x+4=7x+18 | | 3x-5=7x+1 | | 9(x+8)-6= | | x^2-7x-75=0 | | 0.4(x+23)=8 | | 51z(21)=58 | | p-24=-49 | | k/7=10 | | M-9=8 | | 5(x-3)=.5(x-6)+.5(x+8) | | 5c^2-35c=0 | | 3x+4=33 | | 3y^3-11y-4y=0 | | 5(x-9)=.5(x-6)+.5(x+8) | | 5m+10=20m-10 | | -15x=-6 | | 3y+7[8(3y-7)-(2y+2)]+7= | | 7(x-1)=49 | | -4x=o | | 4n+2=5n-6 |